Mechanical Properties in Metal–Organic Frameworks: Emerging Opportunities and Challenges for Device Functionality and Technological Applications. Issue 37 (17th November 2017) - Burtch, Nicholas C.; Heinen, Jurn; Bennett, Thomas D.; Dubbeldam, David; Allendorf, Mark D.
Abstract: Some of the most remarkable recent developments in metal–organic framework (MOF) performance properties can only be rationalized by the mechanical properties endowed by their hybrid inorganic–organic nanoporous structures. While these characteristics create intriguing application prospects, the same attributes also present challenges that will need to be overcome to enable the integration of MOFs with technologies where these promising traits can be exploited. In this review, emerging opportunities and challenges are identified for MOF‐enabled device functionality and technological applications that arise from their fascinating mechanical properties. This is discussed not only in the context of their more well‐studied gas storage and separation applications, but also for instances where MOFs serve as components of functional nanodevices. Recent advances in understanding MOF mechanical structure–property relationships due to attributes such as defects and interpenetration are highlighted, and open questions related to state‐of‐the‐art computational approaches for quantifying their mechanical properties are critically discussed. Abstract : Mechanical properties endowed by the hybrid inorganic–organic structures of nanoporous metal–organic frameworks create intriguing application prospects for these materials, but can also present critical challenges that will need to be overcome for their integration with relevant technologies. These emerging opportunities and challenges, including advances in understanding their structure–property relationships, and associated experimental and computational characterization techniques, are critically discussed.